1977
DOI: 10.1063/1.323553
|View full text |Cite
|
Sign up to set email alerts
|

Optical and photoconductive properties of discharge-produced amorphous silicon

Abstract: Optical and photoconductive properties of discharge-produced amorphous silicon (a-Si) of the type used in efficient thin-film solar cells have been studied as a function of a wide range of deposition conditions. The optical absorption, optical band gap, photoconductivity, hydrogen content, and the characteristics of the Si-H vibrational mode in a-Si were determined. Both substrate temperature in the range ∼200–400 °C and the type of discharge used are found to be important factors in determining the measured o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(38 citation statements)
references
References 22 publications
0
37
0
1
Order By: Relevance
“…The authors found the corresponding CN 18 O image for the 18 O 2 exposed device to be equivalent with the 18 O image, which they took as evidence that it was (at least) the nitrogen part of the molecule ( Figure 13) that was photo-oxidized. The phenomenon shown in Figure 15 has been mentioned by Norrman et al [203][204][205][206] in several of publications where TOF-SIMS was used in combination with isotopically labeled atmospheres.…”
Section: The Barrier Effectmentioning
confidence: 95%
“…The authors found the corresponding CN 18 O image for the 18 O 2 exposed device to be equivalent with the 18 O image, which they took as evidence that it was (at least) the nitrogen part of the molecule ( Figure 13) that was photo-oxidized. The phenomenon shown in Figure 15 has been mentioned by Norrman et al [203][204][205][206] in several of publications where TOF-SIMS was used in combination with isotopically labeled atmospheres.…”
Section: The Barrier Effectmentioning
confidence: 95%
“…The gap electrode geometry yields the ambipolar secondary photoconductivity. [3][4][5][6][7][8] In this measurement, gap electrodes do not block either carrier. Hence, the photoconductivity is due to the secondary photocurrent of both carriers and will be denoted by SSPC (ie., §econdary electron and §econdary hole Qhoto.Qonductivity).…”
Section: Introductionmentioning
confidence: 78%
“…2 allows the determination of the atomic and mass density of the film. 8,[10][11][12] From here, the total hydrogen content, as well as the content of hydrogen bonded as Si-H (2000 cm -1 ) and in nanovoid (2090 cm -1 ) configurations can be obtained, the latter providing us with a quantitative measurement of film porosity. For simplicity, and due to their inherent similarity, we will use the term "hydrogen void concentration" to refer to both the atomic concentration of hydrogen in the high stretching mode configuration and the film porosity.…”
Section: Methodsmentioning
confidence: 98%